2004
DOI: 10.1103/physrevd.69.104027
|View full text |Cite
|
Sign up to set email alerts
|

Fake supergravity and domain wall stability

Abstract: We review the generalized Witten-Nester spinor stability argument for flat domain wall solutions of gravitational theories. Neither the field theory nor the solution need be supersymmetric. Nor is the space-time dimension restricted. We develop the non-trivial extension required for AdS-sliced domain walls and apply this to show that the recently proposed "Janus" solution of Type IIB supergravity is stable non-perturbatively for a broad class of deformations. Generalizations of this solution to arbitrary dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
460
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(472 citation statements)
references
References 41 publications
12
460
0
Order By: Relevance
“…This would make possible to consider null deformation of solutions like Janus [74], which is conjectured to be dual to an interface CFT [75]. The stability of this ten-dimensional Type 0 solution was proven in [29] using Fake supergravity, while its embedding in N = 2, d = 5 gauged supergravity has been derived in [76], on the line of [28]. The supersymmetric Type II Janus has been recently obtained in [77] and its holographic interpretation discussed in [78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would make possible to consider null deformation of solutions like Janus [74], which is conjectured to be dual to an interface CFT [75]. The stability of this ten-dimensional Type 0 solution was proven in [29] using Fake supergravity, while its embedding in N = 2, d = 5 gauged supergravity has been derived in [76], on the line of [28]. The supersymmetric Type II Janus has been recently obtained in [77] and its holographic interpretation discussed in [78].…”
Section: Discussionmentioning
confidence: 99%
“…The subject has been extensively studied in the literature, mainly as an application/extention of the AdS/CFT correspondence and as phenomenological model with large extra-dimensions (Brane world). The relevance of such configuration justified the derivation of an "effective" supergravity approach [12] known as Fake supergravity [29], valid for any space-time dimensions. The explicit relation of this powerful tool for constructing domain wall solutions, with the full-fledged N = 2 D = 5 gauged supergravity has been first uncovered in [28], and further explored in [46].…”
Section: Bps-domain Walls In Supergravitymentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, however, equation (1.8) does not define the function W (φ) uniquely and hence there may generically exist other functions W (φ) satisfying (1.8) in addition to W o (φ). 2 This has been termed fake supergravity and in this context any function W (φ) that solves (1.8) is called a fake superpotential [2,3,6,7]. In [7] it was shown that any BPS Poincaré domain wall of the form (1.1), defined by a function W (φ) which is not necessarily the true superpotential of a given gauged supergravity,…”
Section: Jhep02(2007)008mentioning
confidence: 99%
“…We will nevertheless continue to call such solutions 'BPS' since they satisfy the first order equations (1.7). They are still special solutions because they allow for the definition of fake Killing spinors via (1.9) with W o (φ) replaced by the fake superpotential W (φ) [2]. 3 The existence of fake Killing spinors implies, in particular, non-perturbative gravitational stability, at least in the absence of naked singularities [9,4,2].…”
Section: Jhep02(2007)008mentioning
confidence: 99%